1997
DOI: 10.1292/jvms.59.409
|View full text |Cite
|
Sign up to set email alerts
|

Distributions of the Cardiac Plexuses and Ganglia in the Beijing Duck.

Abstract: ABSTRACT. Distributions of the cardiac plexuses and cardiac ganglia were gross-anatomically and histologically studied in eight Beijing ducks. The cardiac plexuses consisted of two components, the cardiac nerve arising from the sympathetic trunk and the cranial and caudal cardiac nerves arising from the vagus. Branches of these nerves made the cardiac plexuses on the epicardium. The cardiac plexuses could be divided into the six plexuses, that is, the right and left coronary plexuses, pericardiac transverse si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
1
1
Order By: Relevance
“…Sympathetic postganglionic neurons innervating the heart: In our previous gross-anatomical study, the cardiac sympathetic nerve of the duck was observed to arise from the parasympathetic ganglion T1 or T2, but not from the cervical parasympathetic ganglia [5]. In the present study, however, sympathetic postganglionic neurons innervating the heart were observed in the paravertebral ganglia C15 to T3, especially in the ganglion T1.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Sympathetic postganglionic neurons innervating the heart: In our previous gross-anatomical study, the cardiac sympathetic nerve of the duck was observed to arise from the parasympathetic ganglion T1 or T2, but not from the cervical parasympathetic ganglia [5]. In the present study, however, sympathetic postganglionic neurons innervating the heart were observed in the paravertebral ganglia C15 to T3, especially in the ganglion T1.…”
Section: Discussioncontrasting
confidence: 54%
“…1999 parasympathetic preganglionic neurons innervating the heart of the pigeon were located in the nucleus ambiguus [4]. Recently, distributions of the cardiac plexus and cardiac ganglia were gross-anatomically studied in the Beijing duck [5]. Six cardiac plexuses and cardiac ganglia arising from the sympathetic trunk and the vagus nerve made the particular pattern of the autonomic nerve networks on the heart of the duck.…”
mentioning
confidence: 99%